The The pharmacy workforce in public primary healthcare centers: promoting access and information on medicines - Emilia B. Faraco; Luciano Guimarães; Claire Anderson; Silvana N. Leite (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Background: Only few studies have analyzed the pharmaceutical workforce in primary healthcare centers, and a global recommendation calls for better understanding of the trends that shape workforce development and capacity. Objective: To analyze the distribution of the pharmaceutical workforce in primary healthcare centers in the national health system [Sistema Único de Saúde (SUS)] in Brazil. Methods: The study was conducted using data from the National Survey on Access, Use and Promotion of Rational Use of Medicines in Brazil. Secondary data referring to the socioeconomic indicators of each municipality were obtained from national public databases. Data stratification in geographic regions was considered, and data on workers in the management of the municipal pharmaceutical services and medicines dispensing centers were analyzed. Crude and adjusted prevalence ratios were calculated by Poisson regression in the study investigating the factors associated with low and high-density pharmacists per 10,000 inhabitants. Results: The results showed that most Brazilian municipalities have a rate of 1 or more pharmacist per 10,000 inhabitants in primary healthcare public facilities, with a higher concentration of pharmacists in small municipalities. Even in Brazilian municipalities with lower economic capacity, the conditions of access to medicines and pertinent information on medicines were directly related to the number of pharmacists available in these centers. Conclusions: This study showed a high number of pharmacists in the public health system. The higher density of pharmacists in primary healthcare public facilities correlated to increased access to medicines information and better municipal social development.